Comparison of Quality Measures for Building Outline Extraction. (June 2016) - Potůčková, Markéta; Hofman, Petr
Abstract: To date, numerous automatic building detection methods using lidar data have been developed. However, in most cases the parameters used for the evaluation of the results are not specified, accuracy assessment results cannot be readily compared or no result evaluation is performed at all. In this study, accuracy assessment aspects have been analysed in order to find a generally applicable approach for the comparison of building outline extraction methods. An area‐based evaluation of accuracy has been selected as the most suitable due to its robustness, predictability and comparability between datasets. This assessment can be further supplemented with both object‐ and area‐based evaluations, procured solely with those buildings that were classified as true positives, in order to interpret the extraction results in more detail. In cases where a reference dataset of superior quality (such as low‐altitude aerial imagery) is available, an absolute accuracy evaluation is also relevant.